Assessing lettuce genotypes for yield and quality under aeroponic systems: Toward sustainable nutri-dense urban food production - Anand, S; Singh, S R; Vikas, Y; Lalu, P Y; Mishra, D S; Singh, A K; Aina, Y; Akshay, I P; Prakash, Y (Plant Science Today, 2026)
A evaluation of 5 lettuce (Lactuca sativa L.) varieties (Summer Star, Grand Rapid, Tango, Bingo and Black Rose) was carried out at ICAR-Central Institute for Subtropical Horticulture’s experimental block in Rehmankhera, Lucknow (Uttar Pradesh) India during 2021 to 2022 to assess the phenotypic variability among them in respect of growth and quality parameters under uniform agronomic conditions in aeroponic system. Significant differences were recorded in morphological traits including plant weight, plant height, leaf length and width, total leaf weight, stem diameter, root characteristics, number of leaves per plant, leaf area index and yield. Bingo showed the highest plant (345.50 g) and leaf weight (293.25 g), imputed its compact leaf structure while Tango represented highest plant height (29.25 cm), leaf length (23.01 cm), root length (41.23 cm), leaf area index (1.03), number of leaves (25.83) and total chlorophyll content (0.68 mg/g FW), refereeing strong vegetative vigour. Summer Star observed the highest yield (213.15 q/ha), along with superior leaf width, stem diameter and root weight, suggesting better overall biomass accumulation. Quality traits also have significant variation among the varieties. Black Rose recorded the highest vitamin C (15.80 mg/100 g) and total carotenoids (7.97 mg/100 g), may be due to its red pigmentation. While chlorophyll a content was not significantly observed, chlorophyll b and total chlorophyll value varied significantly among varieties, with Tango and Black Rose performing best. Dry matter content showed no significant variation among the varieties, while it is an important post-harvest trait. The findings highlight the substantial phenotypic variability among lettuce varieties, offering valuable insight for breeding programs focused on improving yield, market appeal and nutritional quality under aeroponic system. This study reinforces the importance of strategic varietal selection for enhancing lettuce productivity and functional quality also aeroponic system where provided the uniform soil media and environment condition retreated the value of germplasm collection and evolution for further breeding program.